The Impact of Chorionicity on Pregnancy Outcome and Neurodevelopment at 2 Years Old Among Twins Born Preterm: The EPIPAGE-2 Cohort Study. Issue 6 (June 2021) - Tosello, B.; Garbi, A.; Blanc, J.; Lorthe, E.; Foix-L'Hélias, L.; D'Ercole, C.; Winer, N.; Subtil, D.; Goffinet, F.; Kayem, G.; Resseguier, N.; Gire, C.
Abstract : (Abstracted from BJOG 2021;128:281–291) Overall, as many as 60% of twins are born preterm, and are therefore at risk for neonatal and long-term complications. Some evidence has shown that outcomes for preterm twins differ by chorionicity-monochorionic (MC) versus dichorionic (DC).